Development of Physics Teaching Material with Problem-Based Learning to Train Students’ Problem-Solving Skills - Muhammad Rezki Rahman; Suyidno Suyidno; Suryajaya Suryajaya (Jurnal Ilmiah Pendidikan Fisika, 2023)
In the era of Industry 4.0, problem-solving skills are crucial to address life's increasingly complex and diverse challenges. However, these skills are often not adequately cultivated in schools. This study aims to describe the suitability of physics teaching materials using problem-based learning (PBL) to enhance students' problem-solving skills in the topic of light and optical instruments. This research employs the Dick and Carey development model, involving five validators, ten students in a limited test, and 15 students in an extensive trial. Data is collected using validation instruments, observation of learning, and problem-solving tests. The results of the study indicate that the validation results of physics teaching materials, including lesson plans, teaching materials, student worksheets, and problem-solving tests, are 93, 92, 90, and 92, respectively, with a "very valid" rating. Furthermore, PBL activities in the limited and extensive trials are 84 and 86, respectively, with a "practical" categorization. In conclusion, the physics teaching materials developed using PBL are suitable for training problem-solving skills in physics education. These materials can be applied in secondary school-level education, particularly for light and optical instruments, to enhance students' problem-solving abilities.